2007
DOI: 10.2337/dc06-2559a
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity and Risk of Gestational Diabetes Mellitus

Abstract: OBJECTIVE -Numerous studies in the U.S. and elsewhere have reported an increased risk of gestational diabetes mellitus (GDM) among women who are overweight or obese compared with lean or normal-weight women. Despite the number and overall consistency of studies reporting a higher risk of GDM with increasing weight or BMI, the magnitude of the association remains uncertain. This meta-analysis was conducted to better estimate this risk and to explore differences across studies. We used a Bayesian model to perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
564
2
38

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 930 publications
(639 citation statements)
references
References 51 publications
35
564
2
38
Order By: Relevance
“…This is consistent with the results of previous studies. A recent meta-analysis concluded that the risk for development of GDM is two and four times higher in overweight and obese women respectively [10]. We also found that neonates born to overweight women were significantly more likely to be large for gestational age.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This is consistent with the results of previous studies. A recent meta-analysis concluded that the risk for development of GDM is two and four times higher in overweight and obese women respectively [10]. We also found that neonates born to overweight women were significantly more likely to be large for gestational age.…”
Section: Discussionsupporting
confidence: 61%
“…There is a large body of evidence correlating extremes of prepregnancy or first trimester BMI with adverse obstetric outcomes [5][6][7][8][9][10][11][12][13][14][15][16]. Although weight gain in the second and third trimesters has been studied [17], this is the first study evaluating the role of second trimester BMI in prediction of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Women who are overweight or obese prepregnancy are significantly more likely to develop gestational diabetes, preeclampsia, and labor and delivery complications (e.g., labor induction, caesarean delivery for infant distress, and postpartum hemorrhage). [3][4][5][6] Research using the earlier 1990 Institute of Medicine (IOM) guidelines indicated that many pregnant women gained in excess of the recommended gestational weight gains; specifically, 40%-49% of normal weight women and 59%-77% of overweight/obese women exceeded the 1990 IOM weight gain guidelines. [7][8][9] Furthermore, revisions to the IOM gestational weight gain guidelines in 2009, which provide more restrictive weight gain recommendations for obese women than those offered in the 1990 recommendations, will likely make it more challenging for women who are obese prepregnancy to gain in compliance with the guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Historic risk factors for macrosomia have included increased maternal weight and excessive weight gain, [5][6][7][8] but they are also associated with the occurrence of GDM in and of itself. [9][10][11][12][13] As such, the quantitative relationship and interaction between these various attributes has remained elusive.…”
Section: Introductionmentioning
confidence: 99%